THE ROLE OF RIDDLES IN TEACHING LOGICAL THINKING - Toshtemirova Kamola Absattarovna (International Journal of Innovations in Engineering Research and Technology, 2021)
From this paper we will see how guessing riddles sharpens and disciplines the mind, teaching children to have clear logic, reasoning and proof. Solving riddles develops the ability to analyze, generalize, forms the ability to independently draw conclusions, inferences.